(untitled) (Scientific journal of the Fergana State University, 2024)
The statistics show the factors influencing the functional development of landscapes using the example of the Fergana region. Among those influencing the functional development of landscapes, geological-geomorphological, hydrological and climatic factors and their relationships are especially justified. Scientific conclusions were formed based on an analysis of literature on the topic and field research.